Morphological segmentation of physiographic features from DEM - Sathymoorthy, D.; Palanikumar, R.; Sagar, B. S. D. (TAYLOR & FRANCIS LTD, 2007)
A terrain can be segmented into three predominant physiographic features; mountains, basins and piedmont slopes. The objective of this paper is to develop a mathematical morphological based algorithm to segment the terrain of a digital elevation model (DEM) into the three predominant physiographic features. Ultimate erosion is used to extract the peaks and pits of the DEM. Conditional dilation is performed on the peaks and pits of the DEM to extract the mountain and basin pixels, respectively. The unclassified pixels are assigned as piedmont slope pixels. The combination of the mountain, basin and piedmont slope regions form the physiographically segmented DEM. The effectiveness of the proposed physiographic segmentation algorithm is tested by implementing it on the Global Digital Elevation Model (GTOPO30) of the Great Basin, Nevada, USA.